The testaments [compact disc, unabridged] - Atwood, Margaret, 1939- (Random House Audio, 2019)
This sequel to The Handmaid's Tale picks up the story fifteen years after Offred stepped into the unknown, with the explosive testaments of three female narrators from Gilead.